2016
DOI: 10.2147/cia.s95362
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of use, and tolerance of, medium-chain triglyceride medical food in the management of Japanese patients with Alzheimer’s disease: a prospective, open-label pilot study

Abstract: ObjectivesThis is the first clinical trial of this type in Japan, designed to analyze two important aspects of Alzheimer’s disease (AD) management using medium-chain triglycerides. Axona was administered for 3 months (40 g of powder containing 20 g of caprylic triglycerides). We used an indurating, four-step dose-titration method (from 10 to 40 g per day) for 7 days before the trial, and examined the tolerance and adverse effects of this intervention. We also investigated its effect on cognitive function in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 32 publications
0
67
1
2
Order By: Relevance
“…However, because the total score of the ADAS-cog is 70 points (11), the improvement in the ADAS-cog score in both studies was very small. A recently conducted intervention study showed that addition of 20 g of caprylic triglycerides for 3 mo did not improve cognitive function (MMSE and ADAS-cog score) in 22 Japanese AD patients, even in those patients without the ApoE4 allele (12). Considering the marked increase in the scores of the NM scale and the significant increase in MMSE points in our study, better effects on cognitive function might be observed with a smaller dose of MCTs (6 g).…”
Section: Discussioncontrasting
confidence: 47%
“…However, because the total score of the ADAS-cog is 70 points (11), the improvement in the ADAS-cog score in both studies was very small. A recently conducted intervention study showed that addition of 20 g of caprylic triglycerides for 3 mo did not improve cognitive function (MMSE and ADAS-cog score) in 22 Japanese AD patients, even in those patients without the ApoE4 allele (12). Considering the marked increase in the scores of the NM scale and the significant increase in MMSE points in our study, better effects on cognitive function might be observed with a smaller dose of MCTs (6 g).…”
Section: Discussioncontrasting
confidence: 47%
“…However, with patients without ApoE4 allele one of the nutritional options to improve mild cognitive impairments is adding medium chain triglycerides to the diet (Page et al, 2009, Farias et al, 2014, Sharma et al, 2014, Fernando et al, 2015, Hertz et al, 2015, Ohnuma et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…2 We previously reported that only patients without Apolipoprotein E4 (ApoE4) and a Mini-Mental State Examination (MMSE) score >14 could show cognitive improvement after administration of Axona. 3 This time, by re-analyzing our previous data, we investigated which aspect of cognitive function was the most improved by MCT/ketones. 3 Twenty-two previously enrolled Japanese patients with mild-to-moderate sporadic AD were re-analyzed.…”
mentioning
confidence: 99%
“…3 This time, by re-analyzing our previous data, we investigated which aspect of cognitive function was the most improved by MCT/ketones. 3 Twenty-two previously enrolled Japanese patients with mild-to-moderate sporadic AD were re-analyzed. 3 The patients took 40-g Axona per day for 90 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation